Mollusk richness and vertical distribution along the rocky shore of Islay, Arequipa, Southern Peru - Tejada-Pérez, Cristian A. (2018)
The coastline is a heterogeneous ecosystem that includes a supralittoral fringe, a midlittoral zone, and an infralittoral fringe, with mollusk species that serve as indicators of vertical zonation. This study contributes to the knowledge of richness and vertical distribution of intertidal mollusks in Islay, Arequipa, Peru. An intensive search was conducted during November and December 2013 to determine richness. A total of 3 25x25 cm grids where located perpendicularly to the seashore with 14 repetitions in each of the 7 study sites, to establish their vertical distribution. A Principal Component Analysis (PCA), nonmetric multidimensional scaling (nMDS) and rank-abundance curves were used to determine vertical distribution. In addition, an Analysis of Similarities (ANOSIM) was utilized to determine differences between mollusk compositions between study sites and subzones. A total of 57 taxa were found, where Echinolittorina peruviana was the most representative species in the supralittoral fringe, Perumytilus purpuratus in the midlittoral zone and Tegula atra in the infralittoral fringe. No significant differences were found in the mollusk composition between study sites. However, there were differences among sub-areas, where the midlittoral zone had the greatest richness and abundance of organisms. There were more similarities between the middle and infra-subzones with respect to the supralittoral fringe.